Зварювання металевих виробів та безпека - Березуцький, Вячеслав Володимирович; Хондак, Інна Іванівна (НТУ "ХПІ", 2018)
У статті проведений аналіз літературних джерел в області основних видів зварювання, а також небезпек, які з ними зв'язані. Розглядається вплив небезпечних і шкідливих виробничих чинників при зварюванні металевих виробів, запропоновано їх класифікацію відповідно до різних процесів зварювання. Приділено увагу речовинам, які вражають робітників при зварюванні і різанні кольорових металів. Описано професійні захворювання, а також заходи і засоби захисту зварників в процесі роботи від впливу шкідливих і небезпечних чинників. Зроблена класифікація найбільш поширених сучасних респіраторів в Україні для зварників. Виконано аналіз наукових досліджень щодо забезпечення безпеки зварювальних робіт. Особливу увагу було приділено питанням утворення чадного газу при різних видах зварювання, розглянуті питання з дослідження впливу СО на зварника і засобів захисту від нього. Розглянуті небезпеки, пов'язані з утворенням чадного газу в зоні зварювання, особливо в замкнених просторах і просторах, які погано вентилюються. Проаналізовані питання безпечної праці осіб, безпосередньо зайнятих при процесах зварювання, і для осіб, які знаходяться в близькості від робочого місця зварника.

The article analyzes literary sources in the field of the main types of welding, as well as the dangers associated with them. The influence of hazardous and harmful production factors on the welding of metal products is considered, and their classification according to different welding processes is proposed. Attention is paid to substances that affect workers when welding and cutting non-ferrous metals. The maximum danger of damage to the health of welders from harmful substances in the form of solid particles, as well as from harmful substances in the form of gaseous particles, in particular, includes: carbon monoxide, nitrogen oxide, nitrogen dioxide, ozone. Industrial sprays are considered as occupational hazards, depending on their biological aggressiveness from the basic physical and chemical properties. Described are occupational diseases, as well as measures and means of protecting welders during work from the influence of harmful and dangerous factors. The classification of the most common mod ern respirators in Ukraine for welders is made. The analysis of scientific researches concerning safety of welding works is executed. Despite the constant improvement of welding methods and welding materials, many hygienic problems of welding production have not been finally solved, so special attention has been paid to the formation of carbon monoxide in various types of welding, the issues of studying the effect of CO on the welder and th e means of protection against it have been considered. The hazards associated with the formation of carbon monoxide in the welding zone are considered, especially in closed spaces and spaces that are poorly ventilated. The issues of safe work of persons directly involved in welding processes and those who are in proximity to the welder's place of work are analyzed.
Welding of metal products and safety
Keywords: зварник; професійне захворювання; зварювальний аерозоль; профілактика; засоби індивідуального захисту; welder; occupational disease; welding aerosol; prevention; personal protective equipment